Comparative study of uniform-MDT and WHO-MDT in pauci and multi bacillary leprosy patients over 18 months of observation - Rani, Neha; Mukherjee, Somnath; Kumar, Prashant; Choudhary, Shyam Sundar (International Journal of Research in Medical Sciences, 2018)
Background: To determine the efficacy of the current WHO-MDT and U-MDT regimen with regard to relapse rate and acceptability of the patients and to compare both regimen in pauci and multi bacillary cases. Methods: Total of 106 leprosy patients aged between 14-60 years attending department of Dermatology, Venerology and Leprosy at RIMS, Ranchi between May 2011 and October 2012 were included in the study and they were allocated alternatively into two groups, U-MDT and WHO-MDT. Patients were followed up for 12 to 18 months for periodic clinical, bacteriological and histopathological assessment. Results: In histopathological assessment of PB cases, after 6, 12 and 18 months, UPB group showed 91%, 100% and 100% improvement as compared to 77.5%, 86.5% and 95.2% in WPB group. Among multi bacillary cases, after 12 months 32% of UMB group of patients became smear negative whereas in WMB group 48% became smear negative. In histopathological assessment after 12 months, in UMB group, 94% patients showed good improvement whereas in WMB group only 77% patients showed good improvement. After 18 months, in UMB group, 50% patients deteriorated and showed poor improvement whereas almost 100% patients showed good improvements in WMB group. Conclusions: In conclusion, U-MDT was observed to be an effective and useful regimen to treat PB patients of leprosy, but in MB patients it was not found to be very effective regimen when compared to WHO-MDT of 12 months duration. Mere acceptability factor of the U-MDT regimen cannot be sufficient for its routine implementation in the general health service.